The The Existence of Law Number 42 Of 1999 on The Execution of Object on Fiduciary Guarantees on Defaulted Debtors - Gatot Eko Yudhoyono; Unggul Basoeky (Journal Equity of Law and Governance, 2025)
Fiduciary means the transfer of property rights based on trust, which gives the debtor a position to retain control of the collateral. The occurrence of fiduciary guarantees through encumbrance by making a notarial deed called the Fiduciary Guarantee Deed. If no settlement is made, direct execution will be carried out in accordance with the provisions of “Article 30 of Law Number 42 of 1999 concerning Fiduciary”. This problem can be resolved through the implementation of court decisions in civil cases. The author in conducting research uses normative juridical research. The research is conducted by examining laws and regulations. Furthermore, the research conducts descriptive analysis through a qualitative approach. The results of the research show that if the debtor defaults, the execution of the fiduciary guaranteed object can be carried out in 3 ways, namely executorial execution, sale of the fiduciary guaranteed object under the authority of the fiduciary recipient through auction and sale under the hand. Factors affecting the execution of fiduciary guarantees include internal and external. Internal factors affecting execution are that the debtor does not understand the law, unilateral determination of default, not stipulated in the deed of agreement and the debtor does not voluntarily submit the object of collateral. Meanwhile, the external factors are that the fiduciary guaranteed deed is not registered by the leasing company, the fiduciary guaranteed certificate is not used as collateral.